Post-licensure, phase IV, safety study of a live attenuated Japanese encephalitis recombinant vaccine in children in Thailand. Issue 2 (5th January 2017) - Chotpitayasunondh, Tawee; Pruekprasert, Pornpimol; Puthanakit, Thanyawee; Pancharoen, Chitsanu; Tangsathapornpong, Auchara; Oberdorfer, Peninnah; Kosalaraksa, Pope; Prommalikit, Olarn; Tangkittithaworn, Suwimon; Kerdpanich, Phirangkul; Techasaensiri, Chonnamet; Korejwo, Joanna; et al.
Highlights: JE-CV is licensed in many countries for the prevention of Japanese encephalitis. A post-marketing study with JE-CV was performed to identify rare adverse events. No new safety risks for JE-CV were identified in a study including 10, 000 children. Abstract: Background: Japanese encephalitis is a mosquito-borne viral disease endemic in most countries in Asia. A recombinant live, attenuated Japanese encephalitis virus vaccine, JE-CV, is licensed in 14 countries, including Thailand, for the prevention of Japanese encephalitis in adults and children. Methods: This was a prospective, phase IV, open-label, multicentre, safety study of JE-CV conducted from November 2013 to April 2015, to evaluate rare serious adverse events (AEs). JE-CV was administered to 10, 000 healthy children aged 9 months to <5 years in Thailand as a primary (Group 1) or booster (Group 2) vaccination. Serious AEs (SAEs), including AEs of special interest, up to 60 days after administration were evaluated. Immediate Grade 3 systemic AEs up to 30 min after JE-CV administration were also described. Results: The median age of participants was 1.1 years in Group 1 and 3.8 years in Group 2. SAEs were reported in 204 (3.0%) participants in Group 1 and 59 (1.9%) participants in Group 2. Among a total of 294 SAEs in 263 participants, only three events occurring in two participants were considered related to vaccination. All three cases were moderate urticaria, none of which met the definition of AEs of special interest for hypersensitivity. AEs of special interest were reported in 28 (0.4%) participants in Group 1 and 4 (0.1%) participants in Group 2; none were considered related to vaccination. Febrile convulsion was the most frequently reported AE of special interest: 25 (0.4%) participants in Group 1; and 2 (<0.1%) in Group 2. There were no cases of Japanese encephalitis reported. No Grade 3 immediate systemic AEs were reported after any JE-CV vaccination. Conclusions: Our study did not identify any new safety concerns with JE-CV and confirms its good safety profile. This study was registered on www.clinicaltrials.gov (NCT01981967 ; Universal Trial Number: U1111-1127-7052).